La huella de los ausentes. Desaparición forzada en Guatemala - Silvia Soriano Hernández (Les Cahiers ALHIM)
The enforced disappearance was planned by the state apparatus, and it’s a practice deeply damaged a sector of society which lives in uncertainty about the whereabouts of their loved ones which were taken alive but did not return and whose destiny is doubtful. That lack of certainty is the tragedy in which families of the disappeared persons lives. The element on which I will deepen is the knowledge of how the victim’s families at the same time that keep searching for their disappeared, they introduced into new and unknown activities despite threats. These victims have a lot to contribute to create a process of politicization that will not stop. Their words, their memories turned into testimony, is the gem from which knowledge can be drawn. Direct testimonies of militants in Guatemala become the epistemological basis to demand justice and for the search of truth.